Evaluasi Pemahaman Tentang Kewirausahaan Studi Kasus Mahasiswa Universitas Dharma Andalas - Lucy Chairoel; Lasti Yossi Hastini; Mellyna Eka Yan Fitri (Jurnal Ekonomi dan Bisnis Dharma Andalas, 2023)
ABSTRACT Entrepreneurial knowledge is important for anyone who is running a business as well as who is going to run a business. One measure of entrepreneurial knowledge is an understanding of the definition of entrepreneurship. The importance of understanding the definition of entrepreneurship because the definition of entrepreneurship provides a basic understanding of the concept, purpose, nature, and type of entrepreneurship. As one of the Private Universities in Padang City, Dharma Andalas University also needs to evaluate the implementation of entrepreneurial education through entrepreneurial knowledge that has been obtained by students in entrepreneurship courses which are compulsory subjects of the University. This study aims to determine the success of entrepreneurial education in providing knowledge about entrepreneurship and entrepreneurs from a definition perspective. This research uses qualitative methods. The selected informants are Dharma Andalas university students from all Study Programs who have participated in the Entrepreneurship course by selection through quota sampling. Data collection techniques using unstructured interviews are then analyzed using a coding process. From the results of the analysis, it is known that students' understanding of entrepreneurship is still not good. Keyword: Entrepreneurship; Understanding of Entrepreneurship; Entrepreneurial education ABSTRAK Pengetahuan kewirausahaan penting bagi siapa saja yang sedang menjalankan bisnis maupun yang akan menjalankan bisnis. Salah satu ukuran tentang pengetahuan kewirausahaan adalah pemahaman tentang definisi kewirausahaan. Pentingnya memahami definisi kewirausahaan karena definisi kewirausahaan memberikan pemahaman dasar tentang konsep, tujuan, sifat, dan jenis wirausaha. Sebagai salah satu Perguruan Tinggi Swasta di Kota Padang, Universitas Dharma Andalas juga perlu melakukan evaluasi pelaksanaan entrepreneurial education melalui pengetahuan kewirausahaan yang telah diperoleh mahasiswa dalam matakuliah kewirausahaan yang menjadi mata kuliah wajib Universitas tersebut. Penelitian ini bertujuan untuk mengetahui keberhasilan entrepreneurial education dalam memberikan pengetahuan tentang kewirausahaan dan pengusaha dari pespektif definisi. Penelitian ini menggunakan metode kualitatif. Informan yang dipilih adalah mahasiswa universitas Dharma Andalas dari semua Program Studi yang telah mengikuti matakuliah Kewirausahaan dengan pemilihan melalui quota sampling. Teknik pengambilan data dengan menggunakan wawancara tidak terstrukturyang kemudian dianalisis menggunakan proses coding. Dari hasil analisis diketahui bahwa pemahaman mahasiswa tentang kewirausahaan masih kurang bagus Kata kunci: Kewirausahaan; Pemahaman tentang Kewirausahaan; Entrepreneurial education